2014
DOI: 10.1027/1864-9335/a000180
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Schachter’s Research on Rejection, Deviance, and Communication (1951)

Abstract: We conducted a replication of the original Schachter (1951) deviation-rejection study. Schachter’s groundbreaking demonstration of the deviation-rejection link has captivated social psychologists for decades. The findings and paradigm were so compelling that the deviation-rejection link is often taken for granted and sometimes may be misrepresented ( Berkowitz, 1971 ; Wahrman & Pugh, 1972 ). Because there have only been two direct replications, one of which by the original author, we believed it was import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Further, group members did not choose him for future interactions (and some actively requested he not be included). These findings were replicated across several studies (Berkowitz & Howard, 1959;Emerson, 1954;Schachter et al, 1954;Tata et al, 1996;Wesselmann, Williams, Pryor et al, 2014). However, deviate individuals are not always treated negatively-sometimes they are perceived as helpful and even revered (Eisinger & Mills, 1968;Moscovici, 1976).…”
Section: The Journal Of Social Psychologymentioning
confidence: 64%
“…Further, group members did not choose him for future interactions (and some actively requested he not be included). These findings were replicated across several studies (Berkowitz & Howard, 1959;Emerson, 1954;Schachter et al, 1954;Tata et al, 1996;Wesselmann, Williams, Pryor et al, 2014). However, deviate individuals are not always treated negatively-sometimes they are perceived as helpful and even revered (Eisinger & Mills, 1968;Moscovici, 1976).…”
Section: The Journal Of Social Psychologymentioning
confidence: 64%
“…Research on exclusion, rejection, and ostracism has a long history. 1 Schachter's (1951) original "deviate" study demonstrated how rejection may be used as a social punishment or a form of social control for a dissenting group member, and this work has recently been replicated (Wesselmann et al, 2014). However, sufficient justification is necessary for exclusion.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“… 9 The Wesselmann et al. [ 58 ] study featured a 3 3 contingency table; all other studies reported in figure 6 featured a 2 2 contingency table. …”
mentioning
confidence: 99%